2010
DOI: 10.3945/jn.109.111427
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ingestion of Long-Chain (n-3) Polyunsaturated Fatty Acids Decreases Fibrinolysis in Men with Metabolic Syndrome

Abstract: Individuals with metabolic syndrome (MetS) often have elevated plasma plasminogen activator inhibitor-1 (PAI-1) and tissue plasminogen activator (t-PA), contributing to an increased risk of cardiovascular disease. PAI-1 and t-PA may be affected by chronic (n-3) long-chain PUFA [(n-3)LCPUFA] supplementation; however, the acute impact of fat ingestion on these risk factors has not been established. Our objective was to investigate the acute effect of (n-3)LCPUFA on plasma PAI-1, t-PA, and platelet aggregation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It has been reported that thromboxane A2 could promote platelet aggregation and vasoconstriction, inducing thrombus formation, but n-3 PUFAs could promote production of prostaglandin, which then decreases the synthesis of thromboxane A2, leading to an anti-thrombosis effect (39). Another study showed that high levels of plasminogen activator inhibitor-1 (PAI-1) and tissue plasminogen activator (t-PA) can increase the risk of platelet aggregation, but n-3 PUFAs can reduce the levels of PAI-1 and t-PA (40). In the present study, GO and KEGG enrichment analysis showed that the biological processes associated with thrombus formation, such as fibrinolysis and blood coagulation, were significantly enriched in the fat-1 transgenic and WT cattle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that thromboxane A2 could promote platelet aggregation and vasoconstriction, inducing thrombus formation, but n-3 PUFAs could promote production of prostaglandin, which then decreases the synthesis of thromboxane A2, leading to an anti-thrombosis effect (39). Another study showed that high levels of plasminogen activator inhibitor-1 (PAI-1) and tissue plasminogen activator (t-PA) can increase the risk of platelet aggregation, but n-3 PUFAs can reduce the levels of PAI-1 and t-PA (40). In the present study, GO and KEGG enrichment analysis showed that the biological processes associated with thrombus formation, such as fibrinolysis and blood coagulation, were significantly enriched in the fat-1 transgenic and WT cattle.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the positive effects of n-3 PUFA were questioned by Montegaard et al [48]; they observed that in individuals with MS, an acute intake of a high n-3 PUFA beverage shifted the balance between plasma PAI-1 and t-PA, which might indicate a lower capacity for fibrinolysis. This potentially negative effect of n-3 PUFA in the post-prandial state is contradictory to the marked reduction in cardiovascoular disease mortality and morbidity observed in prospective studies following chronic consumption of high amounts of fish oil [7,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Intake of omega-3 PUFAs has been associated with increased plasma PAI-1 activity in healthy individuals, in non-insulin-dependent diabetes mellitus patients or patients undergoing coronary bypass surgery [36][37][38]. Interestingly, in a recent study, PAI-1 concentration and activity increased more following high omega-3 PUFAs beverage compared with low omega-3 PUFAs beverage [39].…”
Section: Omega-3 Pufas Smoking Inflammatory Process and Fibrinolytimentioning
confidence: 96%